Evaluasi Jumlah Kebutuhan Nitrogen Dan Energi Pasien Gagal Ginjal Akut Usia Dewasa Di RSUP Dr. Sardjito Periode 2003-2004 - Sary, Yunika (Syifa'Medika, 2010)
A cute renal failure is one of the disease that have suddenly decrease of renalfunction, renal could not to escrate the metabolic product (nitrogen and water) and couldnot balance the acid base. Malnutrition in every stage always happen in the hospital. Thisfact can make an infection, increase the complication, can make respon to the medicaltherapy, and can make the badly result clinic. Because of that, this research have aim toknow the need of nitrogen and energy in adult patient that have acute renal failure, and tosee if there are different significant between amount of nitrogen that patient need and alsoamount of energy that patient need, account with equation of Food and AgricultureOrganization/World Health Organization/United Nations University (FAO/WHO/UNU)and harris Benedict, even the nutrition come from diet therapy and amino acids fromparenteral nutrition. Data collection method with retrospektif and result data analysistwith analitic deskriptive method statistic; paired sample t test. That comparing amount ofnitrogen with energy that patient need, with patient get from diet therapyand amino acidsfrom parenteral nutrition. Data analysis show that the average amount of nitrogen thatpatient need is 9,626 g everyday, the average amount of energy at 56 patient non aminoacids from parenteral nutrition with FAO/WHO/UNU method is 2306,426 kkal and withsimilary of Harris Benedict is 2085,349 kkal, from 12 patient who get amino acids fromparenteral nutrition, data analysis show there are significant differences from hospital, sopositif equivalent happends and there is no significant differences between amount ofenergy that patient need and anergy that patient get from hospital during the treathment,even account with equation of FAO/AHO/UNU and with Harris Benedict.